THERAPEUTIC ANTIBODY TARGETING WISP1 PROTEIN - YAWORSKY, Paul; DOWER, Gabriela; FETHEROLF, Morgan; ESPELIN, Christopher; DEVINE, Erin; TAVARES, Daniel (2025)
Provided herein are antibodies and antibody fragments, which specifically bind WNT1-inducible-signaling pathway protein 1 (WISP1). The anti-WISP1 antibodies provided herein bind domain 3 of WISP1 protein and are shown to inhibit WISP1 protein activity. The anti-WISP1 antibodies are contemplated to be effective for treating and preventing fibrosis in a subject in need thereof. In embodiments, the fibrosis is liver fibrosis or lung fibrosis. L'invention concerne des anticorps et des fragments d'anticorps, qui se lient spécifiquement à la protéine 1 de la voie de signalisation inductible par WNT1 (WISP1). Les anticorps anti-WISP1 selon l'invention se lient au domaine 3 de la protéine WISP1 et démontrent une inhibition de l'activité de la protéine WISP1. Les anticorps anti-WISP1 sont envisagés pour être efficaces pour traiter et prévenir la fibrose chez un sujet en ayant besoin. Dans des modes de réalisation, la fibrose est une fibrose hépatique ou une fibrose pulmonaire.